2020
DOI: 10.1007/s11481-020-09923-w
|View full text |Cite
|
Sign up to set email alerts
|

Smooth or Risky Revisit of an Old Malaria Drug for COVID-19?

Abstract: Hydroxychloroquine (HCQ) is an old medication for malaria. In addition to handling this parasitic disease, HCQ is also used to treat a number of autoimmune disorders including rheumatoid arthritis and systemic lupus erythematosus when other medications are not effective. Recently a new viral infection (COVID-19) is rocking the entire world so much that it has already taken more than 200,000 lives throughout the world within the last two months and the World Health Organization was forced to declare it as a pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
(34 reference statements)
0
47
0
1
Order By: Relevance
“…HCQ can potentially interfere with intracellular calcium signaling and prevent dephosphorylation and activation of the transcription factor NFAT. This is one of the mechanisms by which HCQ interfere in T-cell activation and CD 154 transcription also been shown to reduce this glycosylation step [68]. These studies have together motivated healthcare workers to use these drugs as a prophylactic, postexposure prophylactic, and as a curative drug.…”
Section: Immunomodulatory Effectsmentioning
confidence: 97%
“…HCQ can potentially interfere with intracellular calcium signaling and prevent dephosphorylation and activation of the transcription factor NFAT. This is one of the mechanisms by which HCQ interfere in T-cell activation and CD 154 transcription also been shown to reduce this glycosylation step [68]. These studies have together motivated healthcare workers to use these drugs as a prophylactic, postexposure prophylactic, and as a curative drug.…”
Section: Immunomodulatory Effectsmentioning
confidence: 97%
“…Hydroxychloroquine may suppress immune function by interfering with the processing and presentation of antigens, and the production of cytokines. Acidic vesicles, such as endosomes/lysosomes, which are essential for the membrane fusion, act as major locations of action of chloroquine and hydroxychloroquine [2,3,40]. Chloroquine accumulates in lysosomes (lysosomotropism), and by increasing their pH, interferes with the glycosylation of cellular receptor of SARS-CoV-2 and thereby inhibits the infection of virus [14,40].…”
Section: Mode Of Action Of Hydroxychloroquinementioning
confidence: 99%
“…Reduced activation of CD4 ? T cells leads to decreased production of proinflammatory markers and cytokines [14,40]. It has been suggested that autophagy is involved in autoantigen presentation mediated by MHC class II molecules, and activation of T-helper cells [43].…”
Section: Mode Of Action Of Hydroxychloroquinementioning
confidence: 99%
See 2 more Smart Citations